Generalized gamma fading simulation of scintillation disturbed GNSS signals - Nunes, Fernando (2018)
The generalized gamma distribution includes as particular cases different well-known distributions, such as the Nakagami-m. We propose a computationally efficient technique to generate correlated time-series with generalized gamma distribution. This method is useful in the simulation of GNSS signals disturbed by ionospheric scintillation. The technique requires only knowledge of two parameters, besides the definition of a model for the amplitude power spectrum.